The Effect of Physical Work Environment, Work Discipline, and Work Experience on Employee Satisfaction at PT Valdo Sumber Daya Mandiri Palembang - Indra, Muhammad; Halin, Hamid; Purnamasari, Endah Dewi (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the influence of physical work environment, work discipline, and work experience on employee job satisfaction at PT Valdo Sumber Daya Mandiri. The background of this research stems from employee complaints regarding inadequate physical work conditions, inconsistent enforcement of discipline, and generally low levels of work experience. This research uses a quantitative method with a descriptive and causal approach. The population consists of all 95 employees of PT Valdo Sumber Daya Mandiri, with a saturated sampling technique. Data was collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. The results show that partially, physical work environment, work discipline, and work experience have a positive and significant effect on job satisfaction. Simultaneously, the three variables also significantly affect job satisfaction. This study contributes to the development of human resource management practices, particularly in creating a comfortable work environment, fair disciplinary systems, and effective management of employee experience to enhance job satisfaction Keywords: Physical Work Environment, Work Discipline, Work Experience, Job Satisfaction.